2007
DOI: 10.1007/s11255-006-9133-2
|View full text |Cite
|
Sign up to set email alerts
|

Body mass index, body fat percentage, and the effect of body fat mass on SWL success

Abstract: BFP and BFM parameters are also important factors along with the BMI in providing a successful SWL treatment. All the parameters should be considered regarding the success of the treatment and the patients should be informed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
12
0
1

Year Published

2009
2009
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 8 publications
0
12
0
1
Order By: Relevance
“…We also evaluated, whether obesity significantly affects SWL treatment as described for older machines [17,22,23,32]. Comparing normal weight, overweight and obese patients with regard to stone free rate, our data showed that therapy success did not depend on BMI.…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…We also evaluated, whether obesity significantly affects SWL treatment as described for older machines [17,22,23,32]. Comparing normal weight, overweight and obese patients with regard to stone free rate, our data showed that therapy success did not depend on BMI.…”
Section: Discussionmentioning
confidence: 94%
“…Therefore, the present data contrasts that of other studies performed to date.Akay et al. [23] and El‐Nahas et al. [17]reported a significant influence of BMI on stone‐free rate.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have shown that PBF more accurately reflects body composition than BMI, although both BMI and PBF have been used for the evaluation of human health risks such as cardiovascular risk in clinical practice (12,13). A higher PBF and/or BMI often indicates a higher level of cardiovascular risk (14). However, the relationship between PBF and BMI is not linear (15,16).…”
Section: Introductionmentioning
confidence: 99%
“…Urinary total protein-to-creatinine ratio was also determined with the subjects in a nonrecumbent position for C3 h. Finally height, body weight, and sitting blood pressure (reference: systolic and diastolic blood pressure \90th centile for gender, age, and height in subjects less than 18 years of age and \140/90 mmHg in the remaining subjects) were recorded and a complete physical examination performed. Body mass index was calculated as the body weight in kilograms divided by squared height in meters [8,9] and the glomerular filtration rate (reference value: C90 ml/[min. 1.73 m 2 ]) estimated from height and circulating creatinine using the ''height to creatinine equations'' [10].…”
mentioning
confidence: 99%